PENGARUH BONUS DEMOGRAFI, PENGANGGURAN DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAMBI - Putri Putri; Fanny Nailufar (LPPM Universitas Malikussaleh – Indonesia, 2022)
This study examined the effect of demographic bonuses, unemployment, and inflation on economic growth in Jambi Province. This study used secondary data from the Central Bureau of Statistics of Jambi Province during 2000-2021. The data were analyzed using the Vector Error Correction Method (VECM). All tests used in this study were Stationarity Test, Lag Length Criteria Test, VAR Stability Test, Cointegration Test, Granger Causality Test, and VECM Estimation. The results showed that in the short term, the demographic bonus (TPAK) and unemployment had a negative and insignificant effect, while inflation had a positive and insignificant effect on economic growth in Jambi Province. In the long term, Demographic Bonus had a positive and significant effect on economic growth in Jambi Province, while unemployment had a negative and insignificant effect, and inflation had a negative and significant effect on economic growth in Jambi Province.